Supporting Informed Decision Making for Prostate Specific Antigen (PSA) Testing on the Web: An Online Randomized Controlled Trial - Evans, Rhodri; Joseph-Williams, Natalie; Edwards, Adrian; Newcombe, Robert G; Wright, Patricia; Kinnersley, Paul; Griffiths, Jeff; Jones, Mari; Williams, Janet; Grol, Richard; Elwyn, Glyn (JMIR Publications, 2010)
BackgroundMen considering the prostate specific antigen (PSA) test for prostate cancer, an increasingly common male cancer, are encouraged to make informed decisions, as the test is limited in its accuracy and the natural history of the condition is poorly understood. The Web-based PSA decision aid, Prosdex, was developed as part of the UK Prostate Cancer Risk Management Programme in order to help men make such informed decisions. ObjectivesThe aim of this study was to evaluate the effect of the Web-based PSA decision aid, Prosdex, on informed decision making. MethodsA Web-based randomized controlled trial was conducted in South Wales, United Kingdom. Men aged 50 to 75 who had not previously had a PSA test were randomly allocated to two intervention and two control groups. Participants in the intervention groups either viewed Prosdex or were given a paper version of the text. The main outcome measures were the three components of informed decision making: (1) knowledge of prostate cancer and PSA, (2) attitude toward PSA testing, (3) behavior using a proxy measure, intention to undergo PSA testing. Decisional conflict and anxiety were also measured as was uptake of the PSA test. Outcomes were measured by means of an online questionnaire for the Prosdex group, the paper version group, and one of two control groups. Six months later, PSA test uptake was ascertained from general practitioners' records, and the online questionnaire was repeated. Results are reported in terms of the Mann-Whitney U-statistic divided by the product of the two sample sizes (U/mm), line of no effect 0.50. ResultsParticipants were 514 men. Compared with the control group that completed the initial online questionnaire, men in the Prosdex group had increased knowledge about the PSA test and prostate cancer (U/mn 0.70; 95% CI 0.62 - 0.76); less favourable attitudes to PSA testing (U/mn 0.39, 95% CI 0.31 - 0.47); were less likely to undergo PSA testing (U/mn 0.40, 95% CI 0.32 - 0.48); and had less decisional conflict (U/mn 0.32, 95% CI 0.25 - 0.40); while anxiety level did not differ (U/mn 0.50, 95% CI 0.42 - 0.58). For these outcomes there were no significant differences between men in the Prosdex group and the paper version group. However, in the Prosdex group, increased knowledge was associated with a less favourable attitude toward testing (Spearman rank correlation [ρ] = -0.49, P < .001) and lower intention to undergo testing (ρ = -0.27, P = .02). After six months, PSA test uptake was lower in the Prosdex group than in the paper version and the questionnaire control group (P = .014). Test uptake was also lower in the control group that did not complete a questionnaire than in the control group that did, suggesting a possible Hawthorne effect of the questionnaire in favour of PSA testing. ConclusionsExposure to Prosdex was associated with improved knowledge about the PSA test and prostate cancer. Men who had a high level of knowledge had a less favourable attitude toward and were less likely to undergo PSA testing. Prosdex appears to promote informed decision making regarding the PSA test. Trial RegistrationISRCTN48473735; http://www.controlled-trials.com/ISRCTN48473735 (Archived by WebCite at http://www.webcitation.org/5r1TLQ5nK)